TOPOLOGICAL DERIVATIVE - THEORY AND APPLICATIONS - Szulc, Katarzyna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
The paper is devoted to present some mathematical aspects of the topological derivative and its applications in different fields of sciences such as shape optimization and inverse problems. First the definition of the topological derivative is given and the shape optimization problem is formulated. Next the form of the topological derivative is evaluated for a mixed boundary value problem defined in a geometrical domain. Finally, an example of an application of the topological derivative in the electric impedance tomography is presented.